Pelestarian Kearifan Lokal Tari Tradisional Dalam Upaya Meningkatkan Keterampilan Seni - Rohmattuloh; Dwiyan Nur Santosa; Bagas Yoga Pratama (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
Local wisdom is a cultural heritage that reflects the identity and noble values of a society. One form of local wisdom that has an important role in preserving culture is traditional dance. Preserving traditional dance in an educational context, especially in elementary schools, is very important to instill a love of local culture from an early age and improve students' artistic skills. The method used in this research is a descriptive qualitative method, this method was chosen because the problem being studied concerns things that are going on in the school. in this case, it is about ", Preserving the Local Wisdom of traditional dance in an effort to improve the Arts Skills of Elementary School Students there who have implemented traditional dance activities by holding activities such as art festivals, cultural fairs, which can motivate students to work and display their skills. The results of this research underline the importance of preserving local wisdom through teaching traditional dance in elementary schools. The results of research regarding the preservation of local wisdom through traditional dance in elementary schools show several important findings that support these efforts. Data collected from several elementary schools shows that the integration of traditional dance into the school curriculum can have a positive impact on students' artistic skills and strengthen local cultural identity.